Analysis of the Benefits of Intelligent LED Lighting Control Systems in Commercial Environments - Donghong Chen (Journal of World Economy, 2025)
With the increasing emphasis on energy efficiency and cost control in commercial environments, intelligent LED lighting control systems have emerged as a focal point for commercial building managers. This paper aims to evaluate the economic benefits of intelligent LED lighting control systems in commercial settings, using the actual deployment case of 360 LED LLC as a research subject. Through cost-benefit analysis, data analysis, and other methods, this study delves into the comprehensive benefits of intelligent lighting systems in energy conservation, maintenance, and the enhancement of commercial environment quality. The findings reveal that intelligent LED lighting control systems not only significantly reduce energy costs and maintenance expenses but also optimize the lighting environment to enhance customer experience and employee efficiency, ultimately achieving a notable improvement in commercial benefits. The successful application case of 360 LED LLC provides valuable experience and reference for other commercial enterprises, demonstrating the immense potential and application value of intelligent lighting systems in commercial environments.